SMART GARBAGE ALERT SYSTEM USING MACHINE LEARNING (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Now a day, Waste management is one of the primary problem that the world facesirrespective of the case of developed or developing country. The key issue in the wastemanagement is that the garbage bin at public places gets overflowed well in advance before thecommencement of the next cleaning process. It leads to various hazards such as bad odour & ugliness to that place which may cause for spread of various diseases. To avoid all suchhazardous scenario and maintain public cleanliness and health our project is mounted on a smartgarbage system. The main aim project is to develop a smart intelligent garbage alert system for aproper garbage management. The main aim project is to develop a smart intelligent garbage alertsystem for a proper garbage management. Our project proposes a smart AI dustbin which isCollect the Real time dataset of what’s in the Garbage and Classify the Waste. Prepare theDataset for an Image classification. Train the Neural Network and Create a Tensor Flow Modeland Deploy the Model. After it is also interfaced with hardware using ultrasonic sensor. Thesensor values are read and the values are displayed in the LCD. Hence, garbage management isdone by using both image processing and embedded system. Based on the image processingoutput, the respective degradable and non-degradable dustbins are opened by showing relayoperations.